2019
DOI: 10.1177/1059840519865942
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in Parental Caregivers and Children With Type 1 Diabetes

Abstract: The purpose of this cross-sectional, descriptive, pilot study was to examine the correlations in sleep between caregivers (≥18 years) and young (6–12 years) children with type 1 diabetes. Sleep was measured in both parent and child over 7 days using actigraphy and a sleep diary. Parents completed questionnaires on sleep, stress, depressive symptoms, and demographics. Children completed pediatric anxiety and fatigue questionnaires, and A1C (Hemoglobin A1c) was documented at clinic. Descriptive statistics and Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…Sleep in people with diabetes and their relatives are closely linked. Both actigraphy-based and self-reported measures of sleep in children with type 1 diabetes have been associated with the same measures in parents [44,47]. Similarly, greater self-reported sleep quality in adults with type 1 diabetes was related to greater sleep quality in their spouses [35].…”
Section: Sleep In Significant Others Of People With Diabetesmentioning
confidence: 81%
“…Sleep in people with diabetes and their relatives are closely linked. Both actigraphy-based and self-reported measures of sleep in children with type 1 diabetes have been associated with the same measures in parents [44,47]. Similarly, greater self-reported sleep quality in adults with type 1 diabetes was related to greater sleep quality in their spouses [35].…”
Section: Sleep In Significant Others Of People With Diabetesmentioning
confidence: 81%
“…Sleep efficiency was collected as part of the subjective PSQI (Orta et al, 2016) or using sleep diaries (Matthews et al, 2014) and/or based on objective measures (i.e., actigraphy and polysomnography; Macaulay et al, 2019; Meltzer, 2008; Orta et al, 2016). Sleep efficiency in caregivers ranged between 79% and 93% (Daniel et al, 2018; Feeley et al, 2019; Macaulay et al, 2019; Matthews et al, 2014). Sleep efficiency calculated based on subjective reports (i.e., PSQI or sleep diaries) ranged from 79.2% to 91.7%.…”
Section: Resultsmentioning
confidence: 99%
“…Objectively reported sleep duration was included in 10 studies, and caregiver sleep duration ranged from 5.8 to 7.6 hr/night. Of the studies that reported objective measures of sleep, four reported sleep durations of >7 hr, representing 36% of studies (Feeley et al, 2019; Gedaly-Duff et al, 2006; Macaulay et al, 2019; Matthews et al, 2014). Two studies reported that noncaregiver parents self-reported obtaining fewer hours of sleep than caregiver parents (Matthews et al, 2014; Nozoe et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, both average sleep duration and sleep variability have been shown to be associated with diabetes care behaviors (eg, less average sleep duration related to decreased SMBG or more sleep variability related to decreased SMBG) [189,190]. Furthermore, actigraphy-derived data have shown a relationship between HbA 1c and altered sleep (eg, more total sleep time related to lower HbA 1c ) [51,189], found a relationship between sleep in children and sleep in their parents [191], and showed that youth with T1D who have obesity may have different sleep patterns compared with patients with T1D without obesity [192].…”
Section: Using Actigraphy To Identify Relationships Between Daily Factors and T1d Symptoms And Behaviorsmentioning
confidence: 99%